2015
DOI: 10.1200/jco.2014.59.2782
|View full text |Cite
|
Sign up to set email alerts
|

Belinostat in Patients With Relapsed or Refractory Peripheral T-Cell Lymphoma: Results of the Pivotal Phase II BELIEF (CLN-19) Study

Abstract: Monotherapy with belinostat produced complete and durable responses with manageable toxicity in patients with relapsed or refractory PTCL across the major subtypes, irrespective of number or type of prior therapies. These results have led to US Food and Drug Administration approval of belinostat for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
243
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(288 citation statements)
references
References 35 publications
12
243
0
5
Order By: Relevance
“…A third inhibitor, the pan-HDAC inhibitor Belinostat, was also more recently approved for relapsed and refractory PTCL cases [160,161]. The overall responses were 25% for Romidepsin and 26% for Belinostat [162,163]. Additional indications for Romidepsin are currently being evaluated as a combinatorial treatment, for instance, with Bortezomib, Carfilzomib (both proteasome inhibitors), 5-Azacytidine, or CHOP.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…A third inhibitor, the pan-HDAC inhibitor Belinostat, was also more recently approved for relapsed and refractory PTCL cases [160,161]. The overall responses were 25% for Romidepsin and 26% for Belinostat [162,163]. Additional indications for Romidepsin are currently being evaluated as a combinatorial treatment, for instance, with Bortezomib, Carfilzomib (both proteasome inhibitors), 5-Azacytidine, or CHOP.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…Results led to CFDA approval of chidamide in relapsed or refractory PTCL in December 2014.The full report of the pivotal phase II study can be found in a recent publication (22). It would be interesting to compare the results of chidamide with the other three FDA approved PTCL drugs, all derived from their pivotal phase II trials (7)(8)(9)22). While there were similar patient baseline characteristics from these trials in terms of age, gender, years since first diagnosis and prior systemic therapy numbers, a significant difference presented in the pathological subtypes of patients enrolled between the chidamide trial and the others (Table 3).…”
Section: Pivotal Phase II Trialmentioning
confidence: 99%
“…The adverse reaction profile was similar in the BELIEF trial, which is one of the largest safety analyses of belinostat currently available. 22 The most common grade 3/4 adverse events observed in the 120 patients included were thrombocytopenia and neutropenia, occurring in 13% of the patients, respectively. Anemia (10%), dyspnea (6%), pneumonia (6%), and fatigue (5%) were the other common grade 3/4 adverse reactions observed.…”
Section: Safetymentioning
confidence: 99%
“…22 In this single-arm, Phase II clinical trial, patients were eligible for enrollment after failing at least one prior treatment. The primary study objective was to assess the safety and efficacy of single-agent belinostat in refractory or relapsed PTCL.…”
mentioning
confidence: 99%